A multidisciplinary early mobility model for cardiac patients in coronary intensive care unit. (29th July 2021) - Matharsa, S; Selvamani, D; Thakur, R; Mathew, P; Thomas, M; Papasavvas, T
Abstract: Funding Acknowledgements: This is an unfunded project Background Early mobilization is considered as a complex task in an intensive care unit (ICU) and patients are often on prolonged bed rest leading to physical deconditioning. Intensive care early mobility programs have been recognized to be safe and have shown positive outcomes. However, implementing early mobility program as a standard of care remains a challenge. Coronary Intensive Care Unit (CICU) provides complex care for cardiac critically ill patients. In February 2018, the CICU multidisciplinary team (MDT) started a quality improvement project to implement early mobility program in the unit. Purpose This project aimed to investigate the feasibility of implementing an Early Mobility Protocol in CICU to increase the number of patients mobilized to more than 95%. Secondary objective was to explore the impact of the protocol on the mobility level of the patients at the time of discharge or transfer from the CICU. Methods A multidisciplinary mobility task force including Physicians, nurses, physiotherapists and respiratory therapists was formed to analyze the barriers in implementing an early mobility program. A staff survey was conducted to identify the need for a standard early mobility protocol. Root cause analysis and Pareto analysis was done. An evidence based early mobility protocol was developed and implemented. All non-mechanical ventilated patients were included in the first phase and all mechanical ventilated patients were included in the second phase of the project. A standard ICU Mobility scale (IMS) was used for scoring the mobility level of the patients. This quality improvement project is based on "Institute for Healthcare Improvement" model. Periodical staff education and training programs about early mobilization were conducted to improve staff confidence. Change ideas were implemented using multiple Plan Do Study Act cycles. Results The total number of patients included from 1st March 2018 till 31st December 2019 was 2356. This included both the genders. In March 2018, only 68% of non-mechanical ventilated patients were mobilized, that reached to 88% by November 2018. This gradually increased to 100% in May 2019 and is currently sustained at 100%. In November 2019, only 50% of mechanical ventilated patients were mobilized which gradually increased to 66.66% and 75% in middle and end of December 2019. The mean IMS score at discharge or transfer from CICU was "8". From patient-family experience survey, 93.75% of patients perceived that the program was helpful in regaining mobility and 96.25% of patients felt that the program helped in regaining their autonomy. Conclusion: The result shows that it is safe and feasible to implement an early mobility program in a Coronary Intensive Care Unit. A standardized mobility protocol can lead to efficient mobilization practice facilitating early transfers from ICUs without any complications. This could further enhance the collaboration of the MDT members leading to culture change in ICUs.